Heavy silicon isotopic composition of silicic acid and biogenic silica in Arctic waters over the Beaufort shelf and the Canada Basin. Issue 6 (4th June 2016) - Varela, D. E.; Brzezinski, M. A.; Beucher, C. P.; Jones, J. L.; Giesbrecht, K. E.; Lansard, B.; Mucci, A.
Abstract: The silicon isotopic composition of silicic acid (δ 30 Si(OH)4 ) and biogenic silica (δ 30 Si‐bSiO2 ) were measured for the first time in marine Arctic waters from the Mackenzie River delta to the deep Canada Basin in the late summer of 2009. In the upper 100 m of the water column, δ 30 Si(OH)4 signals (+1.82‰ to +3.08‰) were negatively correlated with the relative contribution of Mackenzie River water. The biogenic Si isotope fractionation factor estimated using an open system model, 30 ε = −0.97 ± 0.17‰, agrees well with laboratory and global‐ocean estimates. Nevertheless, the δ 30 Si dynamics of this region may be better represented by closed system isotope models that yield lower values of 30 ε, between −0.33‰ and −0.41‰, depending on how the contribution of sea‐ice diatoms is incorporated. In the upper 400 m, δ 30 Si‐bSiO2 values were among the heaviest ever measured in marine suspended bSiO2 (+2.03‰ to +3.51‰). A positive correlation between δ 30 Si‐bSiO2 and sea‐ice cover implies that heavy signals can result from isotopically heavy sea‐ice diatoms introduced to pelagic assemblages. Below the surface bSiO2 production zone, the δ 30 Si(OH)4 distribution followed that of major water masses. Vertical δ 30 Si(OH)4 profiles showed a minimum (average of +1.84 ± 0.10‰) in the upper halocline (125–200 m) composed of modified Pacific water and heavier average values (+2.04 ± 0.11‰) in Atlantic water (300–500 m deep). In the Canada Basin Deep Water (below 2000 m), δ 30 Si(OH)4 averaged +1.88 ± 0.12‰, which represents the most positive value ever measured anywhere in the deep ocean. Since most Si(OH)4 enters the Arctic from shallow depths in the Atlantic Ocean, heavy deep Arctic δ 30 Si(OH)4 signals likely reflect the influx of relatively heavy intermediate Atlantic waters. A box model simulation of the global marine δ 30 Si(OH)4 distribution successfully reproduced the observed patterns, with the δ 30 Si(OH)4 of the simulated deep Arctic Ocean being the heaviest of all deep‐ocean basins. Key Points: Deep Arctic silicic acid isotopic signals are the heaviest of all ocean basins Riverine inputs decrease the surface Arctic silicic acid isotopic composition Silicon isotopic distribution in the Arctic follows that of major water masses